Clinical and Ultrastructural Studies of Gelatinous Drop-Like Corneal Dystrophy (GDLD) of a Patient with TACSTD2 Gene Mutation - Ali Masmali; Aljoharah Alkanaan; Hind M. Alkatan; Omar Kirat; Abdullah Ayidh Almutairi; Turki Almubrad; Saeed Akhtar (Journal of Ophthalmology)
Purpose. To describe clinical, molecular genetics, histopathologic and ultrastructural findings of gelatinous drop-like corneal dystrophy (GDLD) (OMIM #204870) in a Sudanese patient. Method. An ocular examination revealed the onset of GDLD in a Sudanese patient (50 years old) at King Khalid Specialist Hospital, Riyadh. The 333 sequence variants in 13 GDLD genes of a DNA sample were screened by Asper Ophthalmics Ltd. It was further confirmed by sequencing. The patient had undergone a penetrating keratoplasty in the right eye. The corneal tissue was processed for histopathology and ultrastructural studies. Results. Slit-lamp observation showed grayish-white multiple superficial corneal nodules of various sizes in the left and right eye. Both corneas became clear after the surgery. The GDLD deposits in the subepithelial region and in the anterior stroma were confirmed by PAS staining and their apple-green birefringence under polarized light. Ultrastructurally, the amyloid fibrils were very thin and grouped in whorl-like structures, which caused splits between and within the stromal lamellae. Collagen fibrils (CFs) and keratocytes had degenerated. A homozygous c.355T > A mutation in exon 1 of the TACSTD2 (M1S1) gene was detected, and alteration of the amino acid (p.Cysl19Ser in NCBI entry NP_002344.2) was observed. Conclusion. In our patient with GDLD, a “c.355T > A” mutation in exon 1 of TACSTD2 was detected and believed to be responsible for the alteration of the amino acid leading to the formation of the amyloid deposits. The deposits caused the ultrastructural degeneration of epithelium, Bowman’s layer, stroma, and keratocytes of the GDLD cornea.